Maternal mental health and risk of child protection involvement: mental health diagnoses associated with increased risk. Issue 12 (16th July 2015) - O'Donnell, Melissa; Maclean, Miriam J; Sims, Scott; Morgan, Vera A; Leonard, Helen; Stanley, Fiona J
Abstract : Background: Previous research shows that maternal mental illness is an important risk factor for child maltreatment. This study aims to quantify the relationship between maternal mental health and risk of child maltreatment according to the different types of mental health diagnoses. Methods: The study used a retrospective cohort of children born in Western Australia between 1990 and 2005, with deidentified linked data from routine health and child protection collections. Results: Nearly 1 in 10 children (9.2%) of mothers with a prior mental health contact had a maltreatment allegation. Alternatively, almost half the children with a maltreatment allegation had a mother with a mental health contact. After adjusting for other risk factors, a history of mental health contacts was associated with a more than doubled risk of allegations (HR=2.64, 95% CI 2.50 to 2.80). Overall, all mental health diagnostic groups were associated with an increased risk of allegations. The greatest risk was found for maternal intellectual disability, followed by disorders of childhood and psychological development, personality disorders, substance-related disorders, and organic disorders. Maltreatment allegations were substantiated at a slightly higher rate than for the general population. Conclusions: Our study shows that maternal mental health is an important factor in child protection involvement. The level of risk varies across diagnostic groups. It is important that mothers with mental health issues are offered appropriate support and services. Adult mental health services should also be aware and discuss the impact of maternal mental health on the family and children's safety and well-being.